Educação em Ciências para uma articulação Ciência, Tecnologia, Sociedade e Pensamento crítico. Um programa de formação de professores - Sandra Isabel Rodrigues Magalhães; Celina Tenreiro-Vieira (Universidade do Minho, 2006)
The development of classroom practices focused on scientific literacy as animportant outcome of schooling forces the re-thinking of science teachersformation. In this sense, this paper reports a study which involved theconception, development, implement and evaluation of an in-service program(IP) focused on the Science Technology Society (STS) education alongwith critical thinking (CT) [STS/CT]. From the obtained results it was concludedthat the in-service program contributed for the teachers to (re)constructconceptions about Science, Technology and Society, to (re)constructknowledge related to the STS orientation and critical thinking and to promotetheir pre-disposition to implement STS/CTdidactic and pedagogic practices